Development of ANEKA-Weighted Product evaluation model based on Tri Kaya Parisudha in computer learning on vocational school - Dewa Gede Hendra Divayana (Cogent Engineering, 2018)
The purpose of this research was to explain the findings of an evaluation model that can be used to evaluate the students’ positive characters in joining the computer learning process. The evaluation aspect used to evaluate the students’ positive characters was the ANEKA values with reference to the concept of Tri Kaya Parisudha (three things cause harmony) as the foundation of the positive character realization. The method used in this research is R&D method, with Borg and Gall model design. The number of respondents involved in simulating this model was 10 respondents. Determination of 10 respondents using purposive sampling technique, so it involves only eight computer teachers and two education evaluators as the stakeholders, has knowledge and experience about the model being developed. The tool used in collecting data from 10 respondents is questionnaires. The analysis technique that can be used to determine the positive characters was weighted product. The simulation results of this evaluation model implementation had been able to show accurate calculations to determine the most dominant positive characters required by students to join the computer learning process optimally.